A Podcast Discussion on the Intracranial Efficacy of Antibody–Drug Conjugates in Patients with EGFR-Mutated NSCLC with Brain Metastases - Melissa L. Johnson; Jessica J. Lin; Adrienne Boire; Melin J. Khandekar; Helena A. Yu (Oncology and Therapy)
Abstract The incidence of brain metastases is higher in patients with non-small cell lung cancer (NSCLC) than in patients with most other cancers, and the development of brain metastases is associated with poor prognosis. The objective of the podcast is to provide information about current and future treatments for brain metastases that develop in patients with EGFR-mutated NSCLC. The panel discusses surveillance and management of patients with brain metastases, different types of currently used treatments, and recent data on the intracranial efficacy of antibody–drug conjugates (ADCs). The panel also discusses current and future studies of ADCs in patients with EGFR-mutated NSCLC with brain metastases. This podcast discussion, among four oncologists (two thoracic oncologists, one radiation oncologist, and one neurologist/neuro-oncologist), is for healthcare professionals (HCPs) at community practices and research institutions.